Approximate analysis methods for asymmetric plan base isolated buildings. - Ryan, Keri L. (Earthquake engineering & structural dynamics.)
An approximate method for linear analysis of asymmetric plan, multistorey buildings is specialized for a single storey, base isolated structure. To find the mode shapes of the torsionally coupled system, the Rayleigh Ritz procedure is applied using the torsionally uncoupled modes as Ritz vectors. This approach reduces to analysis of two single storey systems, each with vibration properties and eccentricities (labelled 'effective eccentricities') similar to corresponding properties of the isolation system or the fixed base structure. With certain assumptions, the vibration properties of the coupled system can be expressed explicitly in terms of these single storey system properties. Three different methods are developed : the first is a direct application of the Rayleigh Ritz procedure; the second and third use simplifications for the effective eccentricities, assuming a relatively stiff superstructures.